Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd004025.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for people with schizophrenia and schizophrenia-like disorders

Abstract: Music therapy as an addition to standard care helps people with schizophrenia to improve their global state, mental state (including negative symptoms) and social functioning if a sufficient number of music therapy sessions are provided by qualified music therapists. Further research should especially address the long-term effects of music therapy, dose-response relationships, as well as the relevance of outcomes measures in relation to music therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 81 publications
6
111
0
6
Order By: Relevance
“…22,[51][52][53] Metaanalysis showed that participation in music therapy (7-78 sessions at a frequency of 1-6 sessions per wk for 1-4 mo) resulted in an improvement in negative symptoms, general mental state and some aspects of cognitive function in patients with schizophrenia. 54 The association between improvement in symptoms, cognition and possibly in musical ability is not clear. 55 Of interest, poststroke studies of indivdiuals with acquired amusia have shown that improvement of verbal memory, attention and executive function was correlated with musical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…22,[51][52][53] Metaanalysis showed that participation in music therapy (7-78 sessions at a frequency of 1-6 sessions per wk for 1-4 mo) resulted in an improvement in negative symptoms, general mental state and some aspects of cognitive function in patients with schizophrenia. 54 The association between improvement in symptoms, cognition and possibly in musical ability is not clear. 55 Of interest, poststroke studies of indivdiuals with acquired amusia have shown that improvement of verbal memory, attention and executive function was correlated with musical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…These four studies showed that treatments utilized music therapy combined with standard procedures improved negative symptoms and social functioning more effectively, than treatments utilizing only standard procedures. Mössler et al [8] published an updated Cochrane review focusing on music therapy for people with schizophrenia. They reviewed 85 papers including papers that had been reviewed by Gold et al [7], and recognized eight reliable studies.…”
Section: Music Therapy For Schizophrenic Patientsmentioning
confidence: 99%
“…[91]. D aneben gibt es interessante Ansätze zur V erbesserung von Negativsymptomen durch Musik-und Kunsttherapie [92][93][94], wobei hier sicherlich weitere Untersuchungen erforderlich sind.…”
Section: Ergänzende Medikamentöse Strategienunclassified